National Ballet of China dancing Roland Petit Recent reviews - Ng, Kevin (Dance Books Ltd., Alton,Hampshire (UK), 2006)
PALABRAS CLAVE: National Ballet of China, Roland Petit.
Dentro del apartado "Dance Now: Recent Reviews"